The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/pec.0000000000001203
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Digital Retinography System Camera in the Pediatric Emergency Department

Abstract: Our data suggest that NMOFP using the DRS camera is a rapid and easy method of obtaining high-quality images of the retina in pediatric ED patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Although access to fundus photographs improved the ED providers' detection rate of relevant funduscopic abnormalities from 0% with direct ophthalmoscopy to 46% on fundus photographs, 6 further image‐interpretation training of the ED providers did not substantially improve their performance 7 . Several additional studies have confirmed that ophthalmoscopy can be replaced by ocular fundus digital cameras that rapidly and easily provide high‐quality fundus photographs of the optic nerve and retina, even without pharmacologic dilation of the pupils 1,8–11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although access to fundus photographs improved the ED providers' detection rate of relevant funduscopic abnormalities from 0% with direct ophthalmoscopy to 46% on fundus photographs, 6 further image‐interpretation training of the ED providers did not substantially improve their performance 7 . Several additional studies have confirmed that ophthalmoscopy can be replaced by ocular fundus digital cameras that rapidly and easily provide high‐quality fundus photographs of the optic nerve and retina, even without pharmacologic dilation of the pupils 1,8–11 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies based primarily in emergency departments (EDs) and outpatient clinics have shown that most nonophthalmologic health care providers are not able to reliably examine the ocular fundus 3–5 . Recent publications have emphasized that nonmydriatic ocular fundus photography can easily replace ophthalmoscopy in EDs and urgent care centers, as well as in neurologic and other adult and pediatric clinics 6–11 . These ocular fundus photographs can be interpreted on site or remotely by ophthalmologists via telemedicine 1,11 .…”
mentioning
confidence: 99%
“…Additionally, the average length of time to obtain the image was 1.8 minutes and the average patient cooperation was rated as 4.4 out of 5 (1 ¼ uncooperative, no images obtained and 5 ¼ very cooperative). 19 Cost, patient satisfaction, and length of stay could all potentially be improved by utilization of such devices.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Numerous other studies have now validated the use of cameras in clinical settings other than adult EDs. [50][51][52][53][54] The feasibility and reliability of nonmydriatic fundus photography in children as young as 22 months was demonstrated in a pediatric ophthalmology clinic. 50 A subsequent study validated the use of a tabletop nonmydriatic camera in children ages 5-12 years in a pediatric ED.…”
Section: Future Applicationsmentioning
confidence: 99%
“…50 A subsequent study validated the use of a tabletop nonmydriatic camera in children ages 5-12 years in a pediatric ED. 51 Another study showed that relatively good images of the optic disc could be obtained in children as young as 2 years without pupillary dilation using a smartphone attached to an ophthalmoscope. 52 The applications of this technology in neurology settings are multiple and go beyond the assessment of papilledema in headache patients.…”
Section: Future Applicationsmentioning
confidence: 99%